Circular RNA circFGFR1 Functions as an Oncogene in Glioblastoma Cells through Sponging to hsa-miR-224-5p - Qian Zhang; Shan Chen; Yingwei Zhen; Peng Gao; Zhenyu Zhang; Hao Guo; Yong Wang (Journal of Immunology Research)
Recently, increased studies have shown the important regulatory role of circular RNA (circRNA) in cancer progression and development, including glioblastoma (GBM). However, the function of circRNAs in glioblastoma is still largely unclear. Here, we state that circFGFR1 is elevated in glioma cells, resulting in aggravated glioma aggravated malignancy. The upregulation of circFGFR1 also promotes glioma growth in mouse xenograft models. Furthermore, CXCR4 level in glioma cells is positively correlated with circFGFR1 level, and higher CXCR4 expression is found in circFGFR1 overexpression groups. The effect of circFGFR1 on glioma malignancy is abolished in CXCR4 knockout cells. Then, RIP, RNA pull-down, and luciferase reporter assay results showed that hsa-miR-224-5p directly binds to circFGFR1 and CXCR4 mRNA. The CXCR4 3′-untranslated region (UTR) activated luciferase activity was reduced with hsa-miR-224-5p transfection, while it is reversed when cotransfected with circFGFR1, indicating that circFGFR1 acts as a hsa-miR-244-5p sponge to increase CXCR4 expression. The hsa-miR-224-5p expression is negatively corrected with the glioma malignancy through inhibiting CXCR4 level. Besides, the circFGFR1-induced regulation in glioma malignancy is also abrogated in hsa-miR-224-5p knockout cells. Taken together, our findings suggest that circFGFR1 plays a critical role in the tumorigenic behaviors in glioma cells by upregulating CXCR4 expression via sponging to hsa-miR-224-5p. These findings provide a new perspective on circRNAs during GBM development.